The pigeon wants a puppy! - Willems, Mo. (New York, NY : Hyperion Books for Children, 2008)
The pigeon really, really wants a puppy, but when a puppy arrives the pigeon changes its mind.
Keywords: Pigeons -- Fiction; Animals -- Infancy -- Fiction; Dogs -- Fiction